What is the impact of World Heritage status and related positioning for a tourist audience on Robben Island's meanings and public narratives? - Ngewu, Mandla (School of Architecture, Planning and Geomatics, 2023)
The advent of democracy brought about changes in the cultural heritage landscape. Cultural heritage used to be a preserve of the rich and experts. Heritage of places is not found lying around for it to be discovered, but it is continually reproduced to suit the needs of that particular society. Reproduction of heritage is due to it being amenable to be used and reused to suit the needs of that grouping. Cultural heritage in South Africa offers is used as an economic tool as it offers easy access for participants to the cultural tourism industry. The capital outlay is usually minimal. Politicians also use cultural heritage to create new identities. In South Africa, during the early stages of democracy, heritage was used to promote national reconciliation and nation-building. Robben Island was used as a flagship institution to open up the cultural heritage space and give voice to those previously denied access or whose heritage was distorted or misrepresented. Robben Island, a place of atrocity stemming from the colonial period, was seen as a beacon of hope and promoted as a symbol of the triumph of the human spirit over adversity. The site's positioning as an economic tool and fostering notions of national unity invariably leads to selecting a layer that will resonate with the nationalist ideals. The exploratory study uses interviews with tour guides and heritage experts to examine the message told to visitors. The results obtained are contrasted with the national legislation, the site's conservation management plans, and UNESCO's requirements for listed sites. At an international level, UNESCO is concerned with preserving the outstanding universal value of sites. The preservation of the heritage at a local level is done through national legislation.